Hierarchy of Values in Qur’anic Hermeneutic of Abdullah Saeed (A Study of Contextual Interpretation in Q.S. Al-Hujurat) - Shinta Nurani (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
This article discusses an interpretation of the Qur’an by Abdullah Said using the contextual interpretation model. However, this paper will focus on how Abdullah Saeed developed the concept hierarchy of values inspired by Fazlur Rahman's thought, how application and implication of this concept in Qur’anic interpretation. Abdullah Saeed developed and formulated the concept hierarchy of values into five levels, including obligatory values, fundamental values, protective values, implementational values, and instructional values. The five hierarchies of values become a complete unified frame as an effort to the contextual interpretation of the Qur’an, especially the ethico-legal verses that mostly fill the daily life of most Muslims based on the understanding of maqashid al-sharia and the concept of good deeds. This study uses a descriptive analysis method and hermeneutic analysis techniques to apply the concept hierarchy of values in the Qur’anic interpretation. The results of this paper are in the contextual interpretation of QS. Al-Hujurat in the 1st-5th verses are instructional value; the 6th and 9th verses are combination of fundamental, protectional and impementational values; the 7th-8th verses and the 14th-18th verses are obligatory value; the 10th verse implementational value; the 11th-13th verses are instructional value. In QS. Al-Hujurat contain the five hierarchical levels of values that have been specifically conceived by Abdullah Saeed